Action of chlorhexidine, zingiber officinale, and calcium hydroxide on candida albicans, enterococcus faecalis, escherichia coli, and endotoxin in the root canals - Valera, Marcia C. [UNESP]; Oliveira, Sarah A.C. [UNESP]; Maekawa, Lilian E. [UNESP]; Cardoso, Flávia G.R.; Chung, Adriana [UNESP]; Silva, Stephanie F.P. [UNESP]; Carvalho, Cláudio A.T. [UNESP] (Jaypee Brothers Medical Publishing, 2016)
Aim: The purpose of this in vitro study was to evaluate the antimicrobial activity of 2% chlorhexidine gel (CHX) as auxiliary chemical substance and intracanal medications on Candida albicans, Enterococcus faecalis, Escherichia coli, and their endotoxins in the root canals. Materials and methods: The study was conducted on 48 single-rooted human teeth divided into four groups (n = 12), according to intracanal medications used: (1) Calcium hydroxide + apyrogenic saline solution (Ca(OH)2 + SS), (2) 20% ginger glycolic extract (GEN), (3) calcium hydroxide + 20% ginger glycolic extract (Ca(OH)2 + GEN), (4) apyrogenic SS (control). Collections were made from the root canal content before preparation (baseline-S1), immediately after instrumentation (S2), 7 days after instrumentation (S3), after 14 days the action of intracanal medication (S4), and 7 days after removal of the intracanal medication (S5). The antimicrobial activity and endotoxin content were analyzed for all collections. The results were statistically analyzed by the Kruskal-Wallis and Dunn tests at a significance level of 5%. Results: After instrumentation with CHX, there was complete elimination of E. coli and C. albicans, except for E. faecalis, which was significantly reduced and then completely eliminated after intracanal medication. There was significant reduction of endotoxin after instrumentation. Comparison of collection after instrumentation and intracanal medication revealed reduction of endotoxins in all groups; this reduction was greater in group Ca(OH)2 followed by the group GEN. Conclusion: It was concluded that the instrumentation using CHX and intracanal medication used were able to eliminate the microorganisms from the root canal; the endotoxins were reduced, yet not completely eliminated.
Keywords: Chlorhexidine; Endotoxins; Intracanal medications; Microorganisms; Zingiber officinale